PRESCRIBING PATTERNS OF ANTIDEPRESSANTS IN WAD MEDANI AREA, SUDAN - Awad Alla, Taj Eldin MI Alaa; Ali, Reem; Mahjoub, Samar; Nader, Wesam (Gezira Journal of Health Sciences, 2011)
Background: The important considerations in prescribing antidepressants are their safety and tolerability. Selective serotonin re-uptake inhibitors (SSRIs) are known to be as equally effective as tricyclic antidepressants (TCAs) with fewer side effects profile and better tolerance. Objective: The primary aim of this study was to determine the prescribing patterns of antidepressants in Wed Medani area. Methodology: This cross-sectional, prospective hospital based study assesses the prescription pattern of antidepressant. It was conducted at Wed Medani Psychiatric Teaching Hospital and Hantoub Psychiatric Asylum and Clinic. 500 psychiatric prescriptions were selected at random using a data collection form and analyzed by SPSS. Result: The most commonly prescribed CNS affecting drugs were antipsychotic agents, antidepressants, and antiepileptics. One hundred and fifty (30%) of the 500 prescriptions contained antidepressants. Selective serotonin reuptake inhibitors were prescribed in 25 (16.7%) prescriptions while TCAs were included in 125 (83.3%). It was observed that only 33 (22%) of antidepressants prescriptions followed standard treatment guidelines. Conclusion: To improve the quality of care and to achieve benefits, treatment should be based on current best research evidence treatment guidelines for therapy of depression.